A genomic footprint of a moving hybrid zone in marbled newts. (5th December 2020) - Arntzen, Jan W.; López‐Delgado, Julia; van Riemsdijk, Isolde; Wielstra, Ben
Abstract: We developed a panel of 44 nuclear genetic markers and applied this to two hybridizing species of marbled newts in the north ( Triturus marmoratus ) and the south ( Triturus pygmaeus ) of the Iberian Peninsula, to investigate pattern and process of interspecific gene flow. The northernmost occurrence of T. pygmaeus genetic material was in a T. marmoratus population north of the Vouga river estuary. This suggested the past presence of a hybrid zone, possibly coinciding with a natural river outlet at ca. 1200 A.D. Since 1808, the species contact may have moved back south to a by then completed, man‐made Vouga channel. We also found evidence for a T. marmoratus genomic footprint in T. pygmaeus from the Serra de Sintra, near Lisbon. In combination with a previously reported southern, relic occurrence of T. marmoratus in between both areas, the data point to the superseding with hybridization of T. marmoratus by T. pygmaeus . We estimate that the species hybrid zone has moved along the Atlantic coast over a distance of ca. 215 km. Abstract : Two species of marbled newts in the Iberian Peninsula engage in a narrow hybrid zone. Molecular and geographical data indicate that the zone has, in recent times, moved northwards along the Atlantic coast, over a distance in excess of 200 km.